PENGGUNAAN METODE INQUIRI DENGAN MEDIA BENDA KONKRET DALAM PENINGKATAN PEMBELAJARAN BANGUN RUANG SISWA KELAS IV SDN 1 BUMIREJO - Laeli Maslikhah, nur (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: Implementing Inquiry Methode By Using Concrete Objects Media To Improve  Dimensional Figures Learning Of The Fourth Grade Students Of Sdn 1 Bumirejo In The Academic Year 2012/2013. This research aims to describe the steps, the problems, and the solutions of inquiry method by using concrete objects media to improve dimensional figures learning of the fourth grade students of SDN 1 Bumirejo in the academic year 2012/2013.The research design used in this research is an action research which was conducted in three cycles. Every cycle includes four activities are planning, acting, observation, and reflection. Analysis technique of data used includes reduction of data, data presentation, and conclusing or verification. Based on the research of the study concludes that implementing inquiry methode by using concrete objects media with precise, can to improve  dimensional figures learning of the fourth grade students of Sdn 1 Bumirejo in the academic year  2012/2013.   Keyword: Inquiri method, concrete objects media, dimensional figures Abstrak: Penggunaan Metode Inquiri dengan Media Benda Konkret dalam Peningkatan Pembelajaran Bangun Ruang Siswa Kelas IV SDN 1 Bumirejo. Tujuan penelitian ini untuk mendeskripsikan langkah, kendala, dan solusi metode inquiri dengan media benda konkret dalam peningkatan pembelajaran bangun ruang siswa kelas IV SDN 1 Bumirejo tahun pelajaran 2012/ 2013. Penelitian ini adalah penelitian tindakan kelas yang dilaksanakan dalam tiga siklus. Tiap siklus terdiri dari empat kegiatan yaitu perencanaan, pelaksanaan, pengamatan, dan refleksi. Teknik analisis data terdiri dari reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Hasil penelitian menunjukkan bahwa penggunaan metode inquiri dengan media benda konkret dengan tepat, dapat meningkatkan pembelajaran bangun ruang siswa kelas IV SDN 1 Bumirejo tahun pelajaran 2012/ 2013.   Kata kunci: Metode inquiri, media benda konkret, bangun ruang